2012
DOI: 10.1158/0008-5472.can-12-1187
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 Blockade Enhances T-cell Migration to Tumors by Elevating IFN-γ Inducible Chemokines

Abstract: Adoptive cell transfer (ACT) is considered a promising modality for cancer treatment, but despite ongoing improvements many patients do not experience clinical benefits. The tumor microenvironment is an important limiting factor in immunotherapy that has not been addressed fully in ACT treatments. In this study, we report that upregualtion of the immunosuppressive receptor PD-1 expressed on transferred T cells at the tumor site, in a murine model of ACT, compared with its expression on transferred T cells pres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
282
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(305 citation statements)
references
References 38 publications
21
282
2
Order By: Relevance
“…We found both in vitro and in vivo that blocking PD-1 significantly enhanced the function of CAR T cells leading to a more lethal hit against the tumor. Unlike other studies that used MHC class I restricted T cells (26,27), we found no increase in the percentage of adoptively transferred Thy1.1 þ T cells in the blood or tumor site following combined therapy compared with control treated mice. Future studies using other qualitative approaches such as luciferase transduced T cells would enable the kinetics of T-cell infiltration to be better defined (27).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We found both in vitro and in vivo that blocking PD-1 significantly enhanced the function of CAR T cells leading to a more lethal hit against the tumor. Unlike other studies that used MHC class I restricted T cells (26,27), we found no increase in the percentage of adoptively transferred Thy1.1 þ T cells in the blood or tumor site following combined therapy compared with control treated mice. Future studies using other qualitative approaches such as luciferase transduced T cells would enable the kinetics of T-cell infiltration to be better defined (27).…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike other studies that used MHC class I restricted T cells (26,27), we found no increase in the percentage of adoptively transferred Thy1.1 þ T cells in the blood or tumor site following combined therapy compared with control treated mice. Future studies using other qualitative approaches such as luciferase transduced T cells would enable the kinetics of T-cell infiltration to be better defined (27). An interesting aspect of the current study was that the strong antitumor effects observed with CAR T cells combined with anti-PD-1 antibody correlated with a significant decrease in the percentage of Gr-1 þ CD11b þ MDSCs at the tumor site.…”
Section: Discussioncontrasting
confidence: 99%
“…Anti-PD-1 mAb after the first injection resulted in partial tumor regression (1/5 mice in anti-PD-1 mAbþp24 fc /EP group and 2/5 mice in anti-PD-1 mAb alone group, respectively; ref. 25). However, this effect was abolished when tumor developed in large volume during second and third vaccination.…”
Section: Therapeutic Cure Of Mesothelioma By Vaccine-elicited Immune mentioning
confidence: 96%
“…Both ILs have been shown to be induced in cuprizonefed animals (81,82). (84), generates a Th1-favored, proinflammatory response (85), appears to be involved in NK cell recruitment (86), drives plasma cell differentiation (87), and has been linked to the trafficking of immune cells into malignant disease sites (88). Furthermore, CXCL10 can inhibit vascular smooth muscle cell proliferation (89), or endothelial cell proliferation in vitro independently of CXCR3 (90).…”
Section: Significance Of the Study Using The Cuprizone Modelmentioning
confidence: 99%